Mapping of meiotic recombination in human preimplantation blastocysts - Ma, Yuanlin; Wang, Jing; Li, Rong; Ding, Chenhui; Xu, Yan; Zhou, Canquan; Xu, Yanwen (G3 : genes - genomes - genetics, 2023)
Abstract Recombination is essential for physical attachments and genetic diversity. The Han Chinese population is the largest ethnic group worldwide, therefore, the construction of a genetic map regarding recombination for the population is essential. In this study, 164 and 240 couples who underwent preimplantation genetic testing for monogenic diseases or segmental rearrangement were included in the analysis. Blastocysts and probands from couples who underwent preimplantation genetic testing for monogenic diseases by single nucleotide polymorphism array were included for recombination analysis. The location of recombination was determined from haplotype phase transitions in parent-offspring pairs at loci where the parents were heterozygous. The genetic map for Chinese in vitro fertilization embryos was constructed by the expectation–maximization algorithm with chip-level data. Our results confirmed that homologous recombination occurred more often in maternal chromosomes, and the age effect was more significant in maternal homologous recombination. A total of 6,494 homologous recombination hotspots (32.3%) were identified in genes of Online Mendelian Inheritance in Man. A uniform association between homologous recombination and aneuploidy was not established. In addition, carriers with identified breakpoints of reciprocal translocations were analyzed, and locations of breakpoints were found partly overlapped with homologous recombination hotspots, implying a possible similar mechanism behind both events. This study highlights the significance of constructing a recombination map, which may improve the accuracy of haplotype analysis for preimplantation genetic testing for monogenic diseases. Overlapping locations of translocation and recombination are worthy of further investigation.